Applications and challenges of the palm biomass supply chain in Malaysia - Zahraee, S.M. (Asian Research Publishing Network, 2017)
Nowadays, biomass is considered as one of the main sources of energy for both developed and developing countries. Biomass is one of the potential resources of renewable energy as the novel solution for consuming and depleting the fossil fuels. Utilization of biomass for bioenergy production is a beneficial alternative to meet the increasing energy demands, reduce the carbon dioxide emission, global warming and climate change. In order to deliver a competitive biomass product, it requires a robust supply chain. This paper summarized the recent literature related to optimizing the biomass supply chain in different countries. Moreover, the barriers and problems related to the palm biomass supply chain in Malaysia and review of some operational, economic and social challenges about the biomass supply chain were investigated. Finally, several recommendations are offered for future development on the relevant fields, such as cost, strategic planning, and policy implication. This study has specific importance and very few studies have been done which reviews the biomass supply chain of Malaysia. © 2006-2017 Asian Research Publishing Network (ARPN).